1947
DOI: 10.1111/j.1476-5381.1947.tb00342.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Drug Antagonists for the Identification and Classification of Drugs

Abstract: A sensitive biological method for the identification of drugs has been described by Chang and Gaddum (1933). It consists in estimating the activity of an unknown substance in terms of a standard, quantitatively, in several different pharmacological tests. As a rule the ratio of activity between standard and unknown in different tests is only constant if the two samples are chemically identical, otherwise the ratio of activity in different tests varies. By this method even closely related substances may be diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1956
1956
1988
1988

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Schild (1947a) has suggested the determination of pA, values as a convenient and quantitative measure of drug antagonism. In subsequent papers (Schild, 1947b;Arunlakshana & Schild, 1959) the identification of agonists which act on the same receptor population was described. Although this method has usually been applied in vitro, several studies were reported recently in which the equivalent of pA2 values were determined in vivo (Cox & Weinstock, 1964;Green & Fleming, 1967;Blane, Boura, Fitzgerald & Lister, 1967;Takemori, Kupferberg & Miller, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…Schild (1947a) has suggested the determination of pA, values as a convenient and quantitative measure of drug antagonism. In subsequent papers (Schild, 1947b;Arunlakshana & Schild, 1959) the identification of agonists which act on the same receptor population was described. Although this method has usually been applied in vitro, several studies were reported recently in which the equivalent of pA2 values were determined in vivo (Cox & Weinstock, 1964;Green & Fleming, 1967;Blane, Boura, Fitzgerald & Lister, 1967;Takemori, Kupferberg & Miller, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…One major difference we have observed between the rat and rabbit aortae is that in rabbit aorta, oxymetazoline is approximately 7 times more potent than noradrenaline whereas in rat aorta, oxymetazoline is approximately 13 fold less potent than noradrenaline (Table 1). This difference in potency of oxymetazoline relative to norad- (Schild, 1947;Furchgott, 1972). This method avoids the problems associated with comparing ED50 values among compounds with differing efficacies.…”
Section: Statistical Evaluationmentioning
confidence: 99%
“…It seems worth recalling that, in contrast to histaminase, the tissue receptors for histamine do not distinguish sharply between primary and secondary amines: the analogue of histamine with a methyl group replacing one of the hydrogens of the terminal amino group is pharmacologically fully active, like histamine (Vartiainen, 1935;Schild, 1947), but it is immune from attack by histaminase.…”
Section: Discussionmentioning
confidence: 99%